Relation of Organic Materials to the Presence of Soil Fauna in the Different Age of Post-Mine Land Rehabilitation - achmad tarmeji (Jurnal Agroekoteknologi Tropika Lembab, 2018)
The research was conducted the status of soil organic matter, soil fauna diversity index types and relationship the presence of organic matter to the soil fauna at different post – mining land rehabilitation age. Research methods throught the stages of direct observation and description in the field as well as analysis in the laboratory. Observasion data was determined based on post-mining land rehabilitation at different age: 1,5 and 10 years. While the data were analyzed in the laboratory was the sample data of land that serves as the data linking organic matter in the presence of soil fauna at different post-mining land rehabilitation age. The result showed that the number of soil fauna on post-mining land rehabilitation increased with increased in the status of organic matter. The longer the age of reclamation, the wider range of soil fauna available. This showed that the longer the age of rehabilitation, this the soil organic matter, the number and diversity of soil fauna was also increased.